Listening to music in psychotherapy - Butterton, Mary (Oxford [u.a.] : Radcliffe Publishing, 2008)
De bedoeling van dit boek is duidelijk: hoe kunnen we gebruik maken van muziek in de psychotherapie?
Includes bibliographical references and index
Keywords: Psychotherapy and music; Music therapy; Psychotherapy -- Methods